Campomanesia velutina leaves extracts exert hypouricemic effects through inhibition of xanthine oxidase and ameliorate inflammatory response triggered by MSU crystals - Araújo,Marcela C.P.M. (2016)
ABSTRACT Gout is a destructive arthritis with a high prevalence worldwide. However, the available therapy is not able to increase life quality in many patients. Campomanesia velutina (Cambess) O. Berg, Myrtaceae, is used in Brazilian folk medicine to treat pain, inflammation and rheumatism. The aim of this study was to evaluate the potential of ethanolic and aqueous extracts from C. velutina leaves to treat hyperuricemia and inflammation in gout arthritis model. Ethanolic extract of leaves and aqueous extract of leaves were in vitro assayed on xanthine oxidase inhibitory effect and in vivo on an experimental model of oxonate-induced hyperuricemia in mice, liver xanthine oxidase inhibition and monosodium urate crystal-induced paw edema model. The extracts at both tested doses (100 and 300 mg/kg) reduced serum urate levels. They were also able to inhibit xanthine oxidase in vitro and in vivo, demonstrating that this might be the mechanism of action underlying the urate-lowering effects. In addition, the extracts showed significant anti-inflammatory activity on monosodium urate crystal-induced paw edema, especially aqueous extract (100 and 300 mg/kg) that reduced edema at all evaluated times. Rutin and myricitrin were identified in ethanolic and in aqueous extracts. In this study, myricitrin was able to reduce serum uric acid levels and inhibit liver xanthine oxidase at the dose of 15 mg/kg. The anti-hyperuricemic activity of rutin has been previously reported. Thus, rutin and myricitrin seem to contribute to the observed effects of ethanolic and aqueous extracts. The results demonstrated the ability of aqueous and ethanolic extracts to lower serum urate levels and to reduce edema induced by monosodium urate crystals. Therefore, they may contribute to the management of gout in the future.